Comparative Study and Critical Analysis of Sustainability Reporting in the Oil and Gas Sector - Thomas, Prakash M. (2006)
Oil and Gas sector is one of the largest and major economic sectors globally. It is also one of the most critical in terms of being a basic driver for all other economic activities worldwide. In the recent times we have seen large scale volatility in Oil and Gas prices and a surge in huge profits for Oil and Gas sector companies. Oil and Gas sector is also one of the major sectors with tremendous impact on not just environmental factors but also on Social and Economic factors. All major Oil and Gas companies in recent years have advocated an Environmental and Social agenda for the greater benefit of the humanity and the environment focussing on Sustainable Development. We have seen a rise in the number of companies in recent years in all sectors reporting on Sustainability Reporting or Triple Bottom Line reporting which in many cases is voluntary in nature. This dissertation focuses on evaluation of Sustainability Reports for five global Oil and Gas companies to study standards of reporting between their head offices and its subsidiaries worldwide. The paper attempts to evaluate on how serious are these companies for sustainability in their day- to-day operations? Are they just mere step for compliance? Are these companies practising double standards based again on regulatory pressures and voluntary nature of the requirement for sustainability reporting? Why do we see variation in reporting standards within the same companies across different geographies? ” The study evaluates various available scoring models to arrive at an appropriate model suited to evaluate Oil and Gas sector sustainability reports. A critical analysis has been done on the finding and recommendations for improving Sustainability Reporting and evaluation ofreports have been given in conclusion.